Literature Review: Tren Penelitian Pendidikan Sains di Era Artificial Intelligence Berdasarkan Analisis Bibliometrik Menggunakan Dimensions AI - Syahrial A; Yulia Hasan; Wahyudi Wahyudi; Muhammad Zuhdi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This study aims to map the trends in science education research in the Artificial Intelligence (AI) era through a bibliometric analysis based on Dimensions AI data for the period 2016–2025. The method used is a descriptive bibliometric analysis with a literature review approach to identify publication patterns, the most productive authors, publishing journals, research field categories, and publication types. The results of the analysis show that there are 2,390 relevant publications, with a significant increasing trend from 2020 to 2025. This indicates that AI-based science education research is developing rapidly towards more adaptive, interactive, and data-driven learning. Therefore, it can be concluded that the trend in science education research in the AI era is getting stronger with increasing collaboration across disciplines and countries, as well as an emphasis on the integration of intelligent technology in pedagogical innovation for effective and sustainable science learning.